A magnetomechanical model for the magnetic memory method. (May 2017) - Shi, Pengpeng; Jin, Ke; Zheng, Xiaojing
Abstract: Steel and other metal alloys are widely used in various industries of the national economy. The structure failure often causes great economic losses, and threatens people's life seriously, therefore the early warning of defect becomes essential to prevent malignant accidents fundamentally. Magnetic memory method is a nondestructive testing technology that can realize the early diagnosis for the ferromagnetic material. One key issue on the magnetic memory method is to establish the quantitative relationship between the shape and size of defect and the surface magnetic memory signals. However, little investigation of this issue restricts its applications in the engineering seriously. In this paper, based on a nonlinear constitutive relation for ferromagnetic materials under a constant weak magnetic field, a magnetomechanical model is established for the magnetic memory method, and its quantitative analysis is also completed by the finite element method. Comparisons of the theoretical results for different magnetomechanical models and experimental data are presented. It shows that theoretical results obtained from the proposed model are more consistent with experimental data, and the proposed magnetomechanical model is applicable for various ferromagnetic materials. A detailed study has also been performed to reveal the effects of load magnitude, defect size, lift-off value on the magnetic memory signals. In addition, a theoretical analysis for the stress concentration problem is presented to demonstrate its feasibility for the early diagnosis. Highlights: A magnetomechanical model for the magnetic memory method is proposed. Comparisons are performed to verify the effectiveness for the proposed model. The proposed model is consistent with experimental phenomenon and applicable for various materials. The factors on affecting the magnetic memory signals are revealed. The early diagnosis is demonstrated by a stress concentration discussion.